The impact of ultrasound decrystallization on enzymatic, antioxidant and antibacterial properties of honey. (July 2021) - Dżugan, Małgorzata; Grabek-Lejko, Dorota; Sidor, Ewelina; Tomczyk, Monika
Abstract: The aim of the research was to assess the impact of liquefying honey by ultrasound processing on its biological activity. Four solid honey samples of different botanical origin were decrystallized by using the ultrasound (sonic bath, 40 kHz, 800 W) and conventional thermal processing (water bath, 40 °C). The biological properties of liquefied and control solid honeys were compared. The ultrasound processing significantly shortened the time of honey liquefaction (from 24 h to 15 min) and delayed of the re-crystallization process compared to conventional method (from 1 to 4 months). Diastase number was comparable in ultrasound and unprocessed honeys, but decreased in conventionally liquefied samples (by 8 to 20.6%) whereas the activity of α -mannosidase and β -galactosidase was insignificantly affected only. Growth inhibition of S. aureus and E.coli by 12.5% water solution of control honey samples was variety-dependent, the lowest for rape (12 and 19%) and the highest for honeydew (32 and 38%, respectively). No significant changes were observed after ultrasound treatment. The antioxidant properties of ultrasound processed honeys were insignificantly reduced up to 8%, while total polyphenols content increased by 3–6% in 75% of tested samples. The hydroxymethylfurfural (HMF) content significantly increased after both treatments (from 31 to 40%), however without exceeding the allowable limit. Industrial relevance: Honey crystallization during storage is natural but undesirable serious problem in processing and marketing of the honey. The ultrasound processing shortened the processing time (saved costs), limited the honey biological activity deterioration, and delayed the re-crystallization of processed honeys. Ultrasound processing is a beneficial non-thermal alternative for conventional liquefying of honey by heating. Highlights: The use of ultrasound treatment to liquefy honey shortened the processing time by 96-fold compared to thermal method. The antioxidant activity and diastase number were insignificantly affected by ultrasound treatment regardless the honey variety. Antibacterial activity of ultrasound-treated honey was not changed.